CORPORATE GOVERNANCE IN MALAYSIA:THE EFFECT OF CORPORATE REFORMS AND STATE BUSINESS RELATION IN MALAYSIA - Nor Azizah Zainal Abidin; Halimah; Nasibah Ahmad (Asian Academy of Management Journal, 2007)
The Asian Financial Crisis in 1997 not only introduced the term of corporate governance but also drew attention of the public about the weaknesses of Malaysian corporate governance practice. After 1998, Malaysian government decided to adopt corporate reform that could enhance the quality of good corporate management practice. This reform is clearly stated in the code and rules of corporate governance. The purpose of this research is to study the significance of implementing the code and rules of corporate governance since the public already realize the close relationship between business and politics. Three companies were chosen as indicators for this study. As a result, it was found that companies which are involved in corporate malpractice but have good relationship with states will always be excluded from the legal corporate action.